Phytochemical compounds loaded to nanocarriers as potential therapeutic substances for alzheimer’s disease-could they be effective? - Polat, Derya Çiçek; Karadağ, Ayşe Esra; Parlar Köprülü, Rabia Edibe; Karantas, Ioannis D.; Mutlu, Gökçe; Çağlar, Emre Şefik; Okur, Mehmet Evren; Üstündağ Okur, Neslihan; Siafaka, Panoraia I. (Bentham Science Publishers, 2022)
Alzheimer's disease accounts for a high percentage of dementia cases in elderly individuals. This type of brain disease is caused by damage to the brain cells affecting the ability of the patients to communicate, as well as their thinking, behavior, and feelings. Although numerous research laboratories focus on advancements in treating Alzheimer's disease, the currently approved pharmacological approaches seem to only alleviate the symptoms. Consequently, there is an urgent need for alternative pharmacological options that can prevent the progressive impairment of neurons. Natural substances were used in ancient times to treat various disorders given their biological activities such as antioxidant, anti-inflammatory, and antiapoptotic properties. Besides, their cost-effectiveness and accessibility to anyone who needs them are their most significant characteristics. Therefore, the possible use of phytochemical compounds for the possible management or even prevention of Alzheimer's disease is currently under investigation. This review article summarizes the present status of Alzheimer's disease diagnosis and underlying mechanisms, the potential phytochemicals and their carriers, along with future perspectives. In the future, natural substances can play a role as an adjunct therapy for neurodegenerative forms of dementia, such as Alzheimer's disease.
Keywords: Alzheimer’s Disease; Phytochemicals; Carriers; Nanotechnology; Adjunct Therapy; Biological Activities